2019
DOI: 10.3390/pathogens8020066
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Bovine Cysticercosis in Two Regions of the State of Tocantins-Brazil and the Importance of Pathogen Identification

Abstract: Bovine cysticercosis, caused by Taenia saginata metacestodes, is the cause of significant economic losses to the meat production chain by condemnation and downgrading of infected carcasses. It is also a public health issue causing human taeniasis. This study evaluated the occurrence of bovine cysticercosis at the meat inspection procedures in slaughterhouses of south and north regions of the Tocantins State in Brazil. Specimens identified as cysts of T. saginata were collected and analyzed by molecular (PCR) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 20 publications
0
6
0
1
Order By: Relevance
“…However, our study suggested that patients with taeniasis accompanied by cysticercosis may need whole-genome analysis to further ascertain whether T. saginata is also responsible for causing human cysticercosis. Despite the widespread availability of molecular identification methods, often tested on proglottids' samples, the sensitivity of detection in cyst samples may be lowered due to DNA degradation within cysts (Figueiredo et al ., 2019 ). Many researchers have reported various mitochondrial/nuclear gene discordances in specimens, indicating potential hybrids between T. asiatica and T. saginata (Nkouawa et al ., 2009 ; Okamoto et al ., 2010 ; Yamane et al ., 2012 ; Ale et al ., 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, our study suggested that patients with taeniasis accompanied by cysticercosis may need whole-genome analysis to further ascertain whether T. saginata is also responsible for causing human cysticercosis. Despite the widespread availability of molecular identification methods, often tested on proglottids' samples, the sensitivity of detection in cyst samples may be lowered due to DNA degradation within cysts (Figueiredo et al ., 2019 ). Many researchers have reported various mitochondrial/nuclear gene discordances in specimens, indicating potential hybrids between T. asiatica and T. saginata (Nkouawa et al ., 2009 ; Okamoto et al ., 2010 ; Yamane et al ., 2012 ; Ale et al ., 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Fragmentation of parasite DNA may have affected our PCR-based methodology, preventing proper amplification of the 800 bp target. The design of different primers to shorten the amplicon length, thus reducing the likelihood of DNA polymerase to encounter template disruptions, would have possibly improved the diagnosis of hydatid cysts as reported for other cestode species [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cattle serve as the intermediate host in the two-host life cycle, while humans represent the definitive hosts. Globally, around 50 million human cases were reported resulting in ~50 thousand fatalities annually [ 1 , 2 ]. Generally, humans get infected by consuming raw or undercooked meat containing infective cysticerci that develop into full grown tapeworms three months later.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the diagnosis of the infection, a visual examination of the cysticerci during the post-mortem examination of carcasses is typically employed for the detection of the parasites. Nevertheless, traditional methods have major drawbacks and limited diagnostic capability [ 1 , 11 ]. Moreover, standard inspection techniques are ineffective for detecting bovine cysticercosis at low concentrations.…”
Section: Introductionmentioning
confidence: 99%